Penguatan Santripreneur melalui Pemberdayaan Ekonomi di Lingkungan Pondok Pesantren - Achmad Zaki Yamani; Muhammad Nur Faiz (Politeknik Negeri Cilacap, 2022)
One of the factors that can support the realization of economic independence in Islamic boarding schools is the Santripreneur program. Al Islahuddiny Islamic Boarding School is one of the boarding schools that facilitates the development of santripreneur as a driver of economic activity in the Islamic boarding school environment. As a form of facilitation for the focus of developing the santripreneur, this community service activity was carried out. The method used in this community service activity is starting with the implementation of a focus group discussion (FGD) in order to formulate the root of the problem and needs and followed by entrepreneurship training by utilizing used goods as items of sale value. The economic empowerment activities of Islamic boarding schools carried out at the Al Islahuddiny Islamic Boarding School have been able to foster the spirit of innovation and creativity of students, while the student involved in this training came from 5 different units, ranging from Madrasah Tsanawiyah (MTs), Madrasah Aliyah (MA) to High Schools. Da’wah Science (STID). Student entrepreneurship training has encouraged the growth of the creation of handmade products that are processed in such a way from the results of recycling plastic waste.